TRANSFORMASI PERHIASAN YANG DIGUNAKAN PADA BAGIAN KEPALA OLEH PENGANTIN PERNIKAHAN DI WILAYAH SUNDA PRIANGAN: THE TRANSFORMATION OF JEWELRY USED ON THE HEAD BY BRIDES IN THE SUNDA PRIANGAN REGION - Mahogany Ramla Lubis; Nansha, Hendhy (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
The Transformation Of Jewelry Used On The Head By Brides In The Sunda Priangan Region. in Jewelry in wedding ceremonies is used as a form of cultural representation. This is also true of the culture in the Sunda Priangan region, which is the center of Tatar Sunda. Bridal jewelry is worn on almost all parts of the bride's body, including the head. The jewelry worn on the heads of both bride and groom plays an important role and has always been worn by brides and grooms throughout history. This indicates that the bridal jewelry has undergone a series of transformations involving various visual and material elements, thereby influencing its functional and cultural values. The transformations that have occurred can be identified historically, dating back to the period when the ancient Sundanese culture was identified with the Hindu-Buddhist-influenced Sunda Kingdom. The identification of this period influenced how, in the Sunda Priangan region, wedding jewelry began to undergo a narrowing of its characteristics. The influence of Islam affected the cultural patterns of the kingdom, and the arrival of colonialism also contributed to the transformations that occurred. Cultural integration has influenced the characteristics of bridal jewelry. The transformation that has taken place can be identified through the bridal jewelry worn on the head, such as the use of crowns, which later transformed into bendo and siger. The transformation is emphasized in its visual and material elements, which can be seen from the changes that have occurred. This also affects the functional and cultural values implicit in jewelry, causing a shift. The identifiable transformation results in a fusion of traditional and modern cultural elements, creating a new aesthetic that is widely used in modern wedding ceremonies.